A flexible thermoelectric nanocoating with layered bridged heterostructure for sensitive thermosensation and high fire safety. (March 2023) - Xie, Huali; Li, Kunquan; Nian, Jiahao; Zheng, Jiajun; Lai, Xuejun; Wu, Wenjian; Su, Xiaojing; Wu, Yunhui; Zhang, Xiaofan
Graphical abstract: Highlights: A flexible thermoelectric nanocoating with layered bridged heterostructure was constructed. The nanocoating accurately detect the temperature-rise phase before ignition. The nanocoating exhibited sensitive and repeatable fire-warning capability. The coated flexible polymer materials self-extinguished in burning tests. Abstract: Organic thermoelectric systems have revealed enticing prospects for repeatable temperature sensing and fire-warning in flexible materials. However, how to achieve high thermoelectric efficiency and highly sensitive thermosensation is still a huge challenge for them. Herein, we demonstrate the fabrication a flexible thermoelectric nanocoating with layered bridged heterostructure through the co-assembly of cellulose modified polypyrrole (PPy-CS) nanowires and MXene nanosheets, which offers compelling opportunity for addressing the above challenge. The layered bridged heterostructure endowed the nanocoating with repeatable sensitive thermoelectric response, through which the nanocoating accurately detected the temperature-rise stage before ignition, and triggered the fire alarm in 1.9 s when encountering fire. Even in the event of a second burning, the nanocoating still triggered the fire alarm in 2.3 s. Meanwhile, the nanocoating formed layered porous structure when being burned and exhibited outstanding flame retardancy. The coated PET film reached a limiting oxygen index of 31.4 % and self-extinguished in vertical burning test. The nanocoating holds great promise for the applications in improving the fire-safety of flexible polymer materials.